Melatonin Secretion during a Short Nap Fosters Subsequent Feedback Learning - Wiesner, Christian D.; Davoli, Valentia; Schürger, David; Prehn-Kristensen, Alexander; Baving, Lioba (Frontiers in Human Neuroscience, 2018)
Sleep helps to protect and renew hippocampus-dependent declarative learning. Less is known about forms of learning that mainly engage the dopaminergic reward system. Animal studies showed that exogenous melatonin modulates the responses of the dopaminergic reward system and acts as a neuroprotectant promoting memory. In humans, melatonin is mainly secreted in darkness during evening hours supporting sleep. In this study, we investigate the effects of a short period of daytime sleep (nap) and endogenous melatonin on reward learning. Twenty-seven healthy, adult students took part in an experiment, either taking a 90min afternoon nap or watching videos (within-subject design). Before and after the sleep vs. wake interval, saliva melatonin levels and reward learning were measured, and in the nap condition, a polysomnogram was obtained. Reward learning was assessed using a two-alternative probabilistic reinforcement-learning task. Sleep itself and subjective arousal or valence had no significant effects on reward learning. However, this study showed for the first time that an afternoon nap can elicit a small but significant melatonin response in about 41% of the participants and that the magnitude of the melatonin response predicts subsequent reward learning. Only in melatonin responders did a short nap improve reward learning. The difference between melatonin-responders and non-responders occurred very early during learning indicating that melatonin might have improved working memory rather than reward learning. Future studies should use paradigms differentiating working memory and reward learning to clarify which aspect of human feedback learning might profit from melatonin.